Media idols and national ‘representation’: Strengthening the national identity in contemporary Japan - Mandujo Salazar, Yunuen Ysela (Universidad Autónoma de Ciudad Juárez, 2016)
From the perspective of the Cultural Studies, building on notions of national identity and theories of cultural and banal nationalism, through extensive interpretative textual analysis of two samples of dominant media phenomena and supported by observations and experiences obtained from fieldwork, this dissertation focuses on the examination of the discourses produced by Japanese power elites about the national identity, embedded in contemporary media banal texts inside the producer society. In Chapter 1, the historic context of Japanese nationalist movements and the construction of the national identity discourses are reviewed, finding that the hegemonic discourse on Japanese identity has maintained some essential traits across time. This discussion leads to evaluate the current political and economic context in which the discourses of interest have developed, resulting in the promotion of Japanese national culture as a mean to solve the nation’s economic issues. In Chapters 2 and 3, through the analysis of the sample media phenomena, it is argued that in Japanese media there is a hegemonic patriotic discourse promoted in banal ways, intended to strengthen the national identity while lessening the provocative nationalist references linked to Japanese military past. The dominant discourse inserted in these phenomena is related to a national representativeness linked to traditional Japanese gender roles disguised in a contemporary and cosmopolitan outfit. Chapter 4, presents the discussion on the incongruences found in such discourse regarding the limited definition of what is considered Japanese and its implications for the relation of Japanese with non-Japanese. In the conclusion, it is argued that the elite-produced discourse on Japan and Japanese people appears to be already naturalized in society, acting as a regime of truth on the national identity. Finally, this study also calls the attention on the potential uses that the elites may try to give to the patriotic feelings that are being promoted by banal texts, which may signify an open and hegemonic resurgence of Japanese nationalist stance in the world.